Daya Tarik Produk Lokal: Otentisitas dan Pengalaman di Nyeduh Kopi - Veronika Helen Kurniawan; Ni Kadek Winda Yanti (CV. ITTC INDONESIA, 2025)
The increasing competition within the coffee shop industry requires businesses to build a strong brand image, offer appealing product variations, and highlight local authenticity as a distinguishing value. Although local coffee shops continue to grow rapidly, empirical studies examining how these factors influence repurchase intention remain limited, indicating the need for further investigation. This study aims to analyze the influence of brand image, product diversification, and local authenticity on repurchase intention, as well as to examine whether customer experience moderates these relationships. A quantitative approach was employed using purposive sampling. A total of 170 respondents who had made purchases at Nyeduh Kopi Tabanan participated in the survey. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the direct relationships among variables and the moderating effect of customer experience. The findings reveal that brand image, product diversification, and local authenticity have a positive and significant influence on repurchase intention. In addition, customer experience strengthens the relationships between brand image and repurchase intention, as well as between local authenticity and repurchase intention, but does not moderate the effect of product diversification. These results emphasize the importance for local coffee shops to reinforce brand identity, expand relevant product variations, and consistently highlight local values. Enhancing customer experience also serves as a key strategy to foster positive consumer perceptions and increase the likelihood of repeat purchases.